PARENT JUDGMENT FACTORS: A PHENOMENOLOGICAL STUDY OF EARLY MARRIAGE IN KUNJOROWESI VILLAGE - Ummu Umayyah; Jihan Kusuma Wardhani; Junaidin Junaidin; Nurulsani S Abd. Latief; Ramon Ananda Paryontri (Institute of Research and Community Service, Institute of Pesantren Kiyai Haji Abdul Chalim, 2022)
Early marriage in Indonesia can occur between the ages of 15-19; this is the developmental phase of adolescence. The phase where the psychological maturity of the individual has not been fully formed, and there is no financial security, to reproductive health problems. Underlying the high rate of early marriage in Indonesia cannot be separated from parents' decision-making factors. The research method used is qualitative by looking at it from the side of phenomenological studies, through interviews and the findings at the research location indicate that parents' decision-making in early marriage for their children is due to 1) low economic factors, for parents who have daughters, by marrying their daughters as soon as possible will reduce the burden of living expenses, for parents who have sons, have the hope that after marriage their children will be more independent and financially responsible, 2) avoid committing adultery, parents worry about their child's promiscuity, pregnant out of wedlock, to the shame of the bad stigma of their child's promiscuity in society 3) and the lack of motive to continue their education, parents do not yet have an understanding of the benefits of higher education for life